VBioindex: A Visual Tool to Estimate Biodiversity - Dong Su Yu; Seung Hwa Yoo (Genomics & Informatics)
Biological diversity, also known as biodiversity, is an important criterion for measuring the value of an ecosystem. As biodiversity is closely related to human welfare and quality of life, many efforts to restore and maintain the biodiversity of species have been made by government agencies and non-governmental organizations, thereby drawing a substantial amount of international attention. In the fields of biological research, biodiversity is widely measured using traditional statistical indices such as the Shannon-Wiener index, species richness, evenness, and relative dominance of species. However, some biologists and ecologists have difficulty using these indices because they require advanced mathematical knowledge and computational techniques. Therefore, we developed VBioindex, a user-friendly program that is capable of measuring the Shannon-Wiener index, species richness, evenness, and relative dominance. VBioindex serves as an easy to use interface and visually represents the results in the form of a simple chart and in addition, VBioindex offers functions for long-term investigations of datasets using time-series analyses.